Burnout Level Emergency Nurses During the Covid-19 Pandemic in Indonesia: Literature Review - Paat, Toar Calvin Christo; Muhammad Al-Amin R Sapeni (Experimental Student Experiences, 2022)
During the Covid-19 Pandemic, Nurses working in emergency rooms are on standby 24 hours a day, mostly in direct contact with patients and have to wear full personal protective equipment which is uncomfortable and can cause workload. Nurses experience psychological and physical pressure to care for patients which is stressful due to increased workload. Exhaustion at work, both physical and mental is called burnout. The purpose of this literature review is to see the burnout level that occurs in emergency nurses during the Covid-19 pandemic in Indonesia. The article search used 3 databases: PubMed; Garuda portal; and Google Scholar. A total of 924 articles were identified and 5 articles were used as references in writing this literature review. The majority of articles concluded that the level of burnout that occurred to nurses on duty in the emergency room during the Covid-19 pandemic that broke out in Indonesia was at a moderate level. However, this cannot be used as a comprehensive conclusion because other studies are needed that look at burnout levels in other regions in Indonesia.